EXPLORING THE ENTREPRENEURIAL CULTURE AMONG FARMERS AND OPPORTUNITIES FOR APPLYING PRECISION FARMING IN THE DEVELOPMENT OF NEW BUSINESS MODELS - Petar Borisov; Stefan Shilev (Journal of Bio-Based Marketing, 2025)
The digitization of European agriculture in the last few years has enabled precision farming to fulfill its potential in organizing the production and marketing of agricultural products. Farmers who are already using precision farming technologies see the main advantages of this type of production management. In economic terms, these technologies make it possible to minimize production costs, achieve economies of scale, overcome labor shortages, etc. In environmental terms, precision farming technology enables the farmer to reduce pressure on the environment. All these benefits provide motivation for more and more new entrepreneurs to adopt precision farming technology. Due to digitalization, we are witnessing the emergence of new business models being developed by a new generation of farmers in the EU. This paper aims to analyze and assess the entrepreneurial culture of farmers and, on this ground, to identify opportunities for the use of precision agriculture in the creation of new business models. The main methods used are survey methods and graphical analysis. The results of the study show that entrepreneurs tend to develop skills in precision agriculture that will give them the ability to impose and develop new business models.